Studi Korelasi Dukungan Sosial Teman Sebaya Dengan Kepercayaan Diri Penderita Acne Vulgaris Di SMPN 1 Wungu Madiun - Devita Anugrah Anggraini; Asrina Pitayanti; Vivin Nurul Jannah; Adhin Al Kasanah (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Self-confidence is the ability to trust one's own abilities and feel positive about oneself. When acne vulgarisappears in adolescence, awareness of the importance of adolescent self-appearance in social life can ultimately affect adolescent self-esteem leading to feelings of lack of confidence. Lack of self-confidence will also cause problems in adolescents such as feeling alienated and closed from their friends, so they cannot show themselves and always feel less than their friends. To increase self-confidence, one of them is by providing social support, the support can come from peers such as supporting, and giving attention. For this reason, the author wants toknow the relationship between peer social support and self-confidence of adolescents with acne vulgaris.The study used a correlational analytic descriptive method with a Cross Sectional approach . The sampling technique uses Stratified Random Sampling with a total of 209 respondents.The results showed that peer social support mostly had a sufficient category of 135 respondents (64.6%), and most of the confidence with a moderate category of 161 respondents (80.4%). Based on the results of the Spearman Rank test analysis, a p-value of 0.000 < a = 0.05 means that there is a relationship between peer social support and the self-confidence of adolescents with acne vulgarisat SMPN 01 Wungu. Based on the results of the analysis, there is a relationship between peer social support and self-confidence of adolescents with acne vulgarisat SMPN 01 Wungu. It is hoped that increased peer social support can be done by adolescents to increase self-confidence so that self-confidence in acne vulgarissufferers increases.